Family support and gains in school readiness: A longitudinal study. (17th September 2017) - Hughes, Claire; White, Naomi; Foley, Sarah; Devine, Rory T.
Abstract : Background: Traditional measures of school readiness are labour‐intensive and do not assess family support. Aims: The current study used the newly developed Brief Early Skills and Support Index (BESSI: Hughes, Daly, Foley, White and Devine 2015) to examine 6‐month longitudinal stability and change in teachers' ratings of young children's school readiness and investigate the role of family support as a predictor of school readiness. Sample: Five hundred and seventy‐eight children (270 boys; 74.2% White British) were included at Time 1 aged 2.58–5.84 years ( M age = 3.98 years, SD = 0.66). Method: Teachers and nursery workers completed BESSI questionnaires for each participant on two occasions separated by 6 months. Results: The four latent factors of the BESSI (i.e., Behavioural Adjustment, Language and Cognition, Daily Living Skills and Family Support) exhibited longitudinal measurement invariance and individual differences in ratings on each factor showed strong stability over time. BESSI ratings were also sensitive to improvements over time. Auto‐regressive models showed that family support and family income (as measured by eligibility for pupil premium support) at Time 1 each uniquely predicted child outcomes at Time 2. Conclusions: These findings highlight the importance of family contexts for children's school readiness.